2001
DOI: 10.1097/00006842-200109000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum Depressive Symptomatology Is Associated With Adverse Obstetric and Neonatal Outcomes

Abstract: Previous studies have shown that antepartum anxiety or stress was associated with growth retardation, premature delivery, and epidural analgesia. Our findings add to this body of evidence, which together suggest an adverse impact of antepartum psychological morbidity on maternal and neonatal well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
277
1
28

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 433 publications
(317 citation statements)
references
References 22 publications
11
277
1
28
Order By: Relevance
“…A previous study (Chung et al, 2001) reported that depression in late pregnancy was associated with an increased risk of epidural analgesia, operative deliveries (cesarean sections and instrumental vaginal deliveries) and supported by another study (Andersson et al, 2004) which found that planned cesarean delivery and epidural analgesia during labour were also significantly more common in women with antenatal depression and/or anxiety.…”
Section: A Fadzil Et Almentioning
confidence: 71%
“…A previous study (Chung et al, 2001) reported that depression in late pregnancy was associated with an increased risk of epidural analgesia, operative deliveries (cesarean sections and instrumental vaginal deliveries) and supported by another study (Andersson et al, 2004) which found that planned cesarean delivery and epidural analgesia during labour were also significantly more common in women with antenatal depression and/or anxiety.…”
Section: A Fadzil Et Almentioning
confidence: 71%
“…Previous studies evaluating maternal depression during the second or third trimester reported prevalence levels of 7.0 % in the USA [6], 13.9 % in England [28], and 17.4 % in Sweden [29] using the EPDS, and 8.7 % in Hong Kong using the Beck Depression Scale [30]. However, the prevalence of depression during pregnancy based on the DSM-III-R Major Depressive Episode in Japan was reported to be 5.6 % [31].…”
Section: Prevalence Of Maternal Depression and Scoring Of Infant Devementioning
confidence: 97%
“…Se ha documentado que las mujeres deprimidas presentan un riesgo incrementado de complicaciones obstétricas (10) , tales como cesárea, partos instrumentados, necesidad de analgesia epidural y mayor número de admisiones a unidades de cuidados intensivos, así como de prematuridad, retardo del crecimiento intrauterino y microcefalia. En el primer año de vida, los hijos de mujeres deprimidas tienen mayor riesgo de que se retrase la lactancia, no se cumplan los esquemas de vacunación, mayor frecuencia de episodios diarreicos y, por ende, desnutrición; además, existen reportes de retardo del desarrollo motor y social (11) .…”
Section: El Embarazo No Deseado Un Factor De Riesgo Para Depresiónunclassified